Individual and Combined Association Between Healthy Behaviors and All-Cause and Premature Mortality: A 22-Year Follow-Up Cohort - De Moraes-Ferrari, G (Elsevier Ltd, 2025)
Objective: To analyze the impact of individual and combined healthy behaviors on all-cause and premature mortality risk in Mexican adults. Methods: Data on physical activity, fruit and vegetable intake, sleep hours, alcohol intake, and smoking from 95,142 adults from the MCPS (Mexico City Prospective Study) were used. All-cause mortality was monitored for up to 22 years, until December 31, 2020. Cox proportional hazards regression was used to assess mortality risk. Results: Physical activity (HR, 0.88; 95% CI, 0.84 to 0.92), fruit and vegetable intake (HR, 0.94; 95% CI, 0.91 to 0.98), no excessive alcohol consumption (HR, 0.86; 95% CI, 0.81 to 0.92), and not smoking (HR, 0.93; 95% CI, 0.89 to 0.97) were individually associated with lower mortality. All-cause mortality risk decreased progressively by 8% (95% CI: 0.86 to 0.99) to 29% (95% CI, 0.63 to 0.81) for each additional healthy behavior attained. Similarly, premature mortality risk decreased by 13% (95% CI, 0.80 to 0.95) to 30% (95% CI, 0.59 to 0.83). Conclusion: Over 22 years, adopting a healthier life was linked with lower all-cause and premature mortality risk, decreasing with the clustering of one additional healthy behavior. Law and policy changes as well as efforts to address the root causes of not adopting healthy behaviors in low- and middle-income countries, such as creating structural conditions for people to engage in physical activity or strong social marketing to raise awareness of the daily consumption of fruits and vegetables, are needed for improving health and delaying mortality. © 2024 Mayo Foundation for Medical Education and Research